Energy dispersive x-ray spectroscopy for nanostructured thin film density evaluation. Issue 2 (8th April 2015) - Prencipe, Irene; Dellasega, David; Zani, Alessandro; Rizzo, Daniele; Passoni, Matteo
Abstract: In this paper, we report on two fast and non-destructive methods for nanostructured film density evaluation based on a combination of energy dispersive x-ray spectroscopy for areal density measurement and scanning electron microscopy (SEM) for thickness evaluation. These techniques have been applied to films with density ranging from the density of a solid down to a few, with different compositions and morphologies. The high resolution of an electron microprobe has been exploited to characterize non-uniform films both at the macroscopic scale and at the microscopic scale.